Mind Shift: Creating Change Through Narrative Learning Cycles - Grainger, Jenny Elizabeth (Auckland University of Technology, 2007)
This thesis explores the process of an annual appraisal strategy, ‘clinical conversation’, from the perspective of seven nurses who were assessed using this technique. The findings demonstrate that clinical conversation is a strategy which facilitates reflection, both as a solitary exercise and with others, to ensure that learning from experience is optimized. The research used a qualitative interpretive approach informed by the model of Grounded Theory espoused by Strauss and Corbin. All eight nurses who were assessed using the clinical conversation strategy were advanced practitioners working within the scope of sexual and reproductive health. Two of the actual appraisals were observed and seven of the nurses were interviewed within eight weeks of being assessed. The outcome of the clinical conversation was primarily one of learning; the acquisition of new insights into self as practitioner. The learning was facilitated through the process of narration; telling the story of clinical practice. Three distinct narrative cycles were identified, each an experiential learning episode. The experience of undertaking a variety of assessment activities created a narrative with self and triggered an internal reflective thinking process; the experience of working with a peer created an additional narrative, a mutual dialogue reflecting back on practice; the experience of sharing practice with an assessor created a further and final narrative, a learning conversation. Each narrative can be seen as a catalyst for change. Primarily, the nurses felt differently about themselves in practice, the way they saw themselves had shifted. Such a change can be described as an alteration in perspective. These alterations in perspective led all nurses to identify ways in which they would change their actual clinical practice. In this way the nurses attempted to align their espoused beliefs about practice with their actual practice. My study shows that each nurse responded differently to each narrative learning cycle: for some the conversation with the assessor was more of a catalyst for change than for others. In this way clinical conversation may be flexible enough to respond to a variety of differing learning styles. Learning was person specific which is an imperative for the continued professional development of already highly skilled clinicians. The implication of the research is that whilst clinical conversation was designed as a tool for appraising clinical competence, its intrinsic value lies in supporting the professional development of nurses.
Keywords: Qualitative interpretive; Nursing; Clinical appraisal; Learning conversation; Reflection; Professional development